The rationale and design of the national peripartum cardiomyopathy registries in Turkey: The ARTEMIS-I and ARTEMIS-II studies - Meral Kayıkçıoğlu; Lale Tokgözoğlu; Ferit Onur Mutluer; Dilek Ural; Murat Biteker (KARE Publishing, 2018)
Objective: Peripartum cardiomyopathy (PPCM) is left ventricular (LV) systolic dysfunction with an ejection fraction of ≤45% occurring in the later stages of pregnancy or soon after delivery. Although various risk factors have been identified, the exact cause of the disease is unknown. Unlike most countries in the European region, Turkey has yet to determine the current PPCM burden. A registry for this purpose does not exist. To close this gap, the A RegisTry of pEripartuM cardIomyopathy in Turkish patientS (ARTEMIS-I and ARTEMIS-II), was planned and endorsed by the Turkish Society of Cardiology. The aim of this manuscript is to describe the rationale and design of the ARTEMIS-I and ARTEMIS-II registries. Methods: ARTEMIS was designed to be the nationwide PPCM registry of Turkey, with the goal of identifying problems and opportunities while improving quality and consistency in the medical care of PPCM patients. A second goal is to determine the clinical characteristics pertinent to patients in this region. The ARTEMIS registry will consist of 2 arms. All secondary and tertiary cardiology centers have been electronically invited to participate in ARTEMIS-I, which will be conducted to assess the current standard of care and outcome measures. Centers will be asked to enroll PPCM patients admitted to their clinic in last 5 years retrospectively. Eligibility criteria will consist of pregnant or early postpartum woman without a previous history of heart failure (HF) or known pathology associated with HF, LV ejection fraction ≤45%, and exclusion of other causes of LV systolic dysfunction. ARTEMIS-II will consist of the prospective enrollment of patients. Conclusion: The nationwide PPCM registries, ARTEMIS-I and ARTEMIS-II, are designed to determine the current status of medical care, provide insights into nature of the disease, and suggest solutions on how to improve care and outcomes in these patients.